(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article deals with the figure of the greatest thinker of the European Renaissance, a prominent public and political figure in France of the era of Henry IV Michel Montaigne (1533-1592), who had a significant impact on the development of linguistic and cultural thought of the era and who is rightfully considered the last humanist of the Renaissance and the first moralist of that Time. His observations about human outlook grestly influenced on the philosophers and scholars of that time and modern world. His work "Experiments" is considered the first of the artistic genre-essay at the time.